2010
DOI: 10.1002/pola.23906
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of 2‐oxazolines: A crossing of cationic ring‐opening polymerization and enzymatic ring‐opening polyaddition

Abstract: Chemistry of 2-oxazolines is involved in the polymer synthesis fields of cationic ring-opening polymerization (CROP) and enzymatic ring-opening polyaddition (EROPA), although both polymerizations look like a quite different class of reaction. The key for the polymerization to proceed is combination of the catalyst (initiator) and the design of monomers. This article describes recent developments in polymer synthesis via these two kinds of polymerizations to afford various functional polymers having completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 131 publications
0
70
0
Order By: Relevance
“…Aspects of advanced macromolecular engineering of polyoxazolines, including side-and end-chain functionalization, synthesis and properties of block and random copolymers, etc., have very recently been assorted by Hoogenboom [9,10], Schlaad et al [11], and Makino and Kobayashi [12]. The use of fatty acid based monomers for the preparation of sustainable poly(2-oxazoline)s was also recently highlighted by Hoogenboom [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspects of advanced macromolecular engineering of polyoxazolines, including side-and end-chain functionalization, synthesis and properties of block and random copolymers, etc., have very recently been assorted by Hoogenboom [9,10], Schlaad et al [11], and Makino and Kobayashi [12]. The use of fatty acid based monomers for the preparation of sustainable poly(2-oxazoline)s was also recently highlighted by Hoogenboom [13].…”
Section: Introductionmentioning
confidence: 99%
“…Not considered are other emerging applications of poly(2-oxazoline)s, for instance in the fields of biomedicine and life sciences, where POXylation is being successfully introduced as an alternative to PEGylation [14], which has very recently been reviewed elsewhere [15]. Rather than trying to present a comprehensive overview of the literature as was done in other recent articles [9][10][11][12][13], it is aimed to introduce the importance and potential of bioinspired poly(2-oxazoline)s based on selected key references from the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Double metal cyanide complex catalysts based on Zn 3 [Co(CN) 6 ] were profitably utilized and microwave irradiation was chosen as heating method, with strong beneficial effects on polymerization times and CO 2 incorporation grade (Dharman et al, 2008). Poly(oxazoline)s are relatively non toxic polymers with attractive properties for biomedical applications, nonetheless they cannot be classified as biodegradable or bio-based polymers: comprehensive reviews about microwave assisted synthesis in this class of products can be found elsewhere (Adams & Schubert, 2007;Makino & Kobayashi, 2010;Wiesbrock et al, 2004).…”
Section: Other Ring Opening Polymerizationsmentioning
confidence: 99%
“…By employing different sugar molecules having a methyl oxazoline side group a variety of natural and synthetic polysaccharides could be produced, in particular some of the most complicated synthetic polymeric structures and synthetic chitin. The fundamental mechanism, although the enzyme interacts with the intermediates and increases the reaction rate considerably, remains a CROP [73]. It is worth noting that polyoxazolines have been shown to be biocompatible and potentially useful as carriers of pharmaceutically active agents [74].…”
Section: Lewis Acidsmentioning
confidence: 99%